Nitrogen and potassium interactions optimized asynchronous spikelet filling and increased grain yield of japonica rice - Weitao Xu; Jianming Li; Jiancheng Feng; Zhenzhu Shao; Yidan Huang; Wenfeng Hou; Qiang Gao (PeerJ, 2023)
Poor grain filling severely reduces rice yield. Fertilizers play a vital role in regulating grain filling, especially nitrogen (N) and potassium (K). In this field study we aimed to investigate the interactive effects of N and K on the asynchronous filling properties of superior and inferior spikelets of japonica rice. We looked at grain filling under three N rates (0, 90, and 180 kg N ha−1) and three K rates (0, 60, and 120 kg K2O ha−1) during 2020 and 2021. Across two years, the results showed that the combined use of N and K on superior and inferior spikelets significantly increased their weight by 1.29 mg and 2.31 mg, their maximum grain filling rate by 0.24 mg d−1 and 0.07 mg d−1, and their average grain filling rate by 0.21 mg d−1 and 0.06 mg d−1, respectively, in comparison with the control (N0K0) treatment. Likewise, K supply increased the average contribution rate of superior and inferior spikelets to yield by 9.1% and 10.0%, respectively. Correlation analysis showed that the grain filling rate of superior and inferior spikelets was an important factor in determining the spikelet weight, whereas the grain filling time was not. We also found that the 1,000-grain weight mainly increased after increasing the spikelets’ maximum grain filling rate and average grain filling rate. Collectively, these results illustrate that the combined use of N and K can optimize the asynchronous filling of superior and inferior spikelets and, in particular, enhance inferior spikelet weight with higher rice yield.